Pengaruh Pemberian Pakan Komersial yang Berbeda pada Pertumbuhan Ikan Nila Oreochromis niloticus - Hamadi, Martha F; Sampekalo, Julius; Lantu, Sartje (e-Journal BUDIDAYA PERAIRAN, 2015)
This research intended to study the growth of nile tilapia and commercial food conversion.  The research was conducted at Laboratory of Nutrition and Fish Feed Technology, Faculty of Fisheries Sam Ratulangi University Manado.  Fish feed used were Comfeed (Treatment A), Bintang (Treatment B) dan Lokal Food  (Treatment C).  Feeding dosage was 5% per body weight per day and feeding frequency was three times a day.  The research used complete randomized design with three treatments each with three replications. Research results showed that treatment A had absolute growth 257,67 g, , relative growth 160,37% and food conversion ratio 1,81 while treatment B had absolute growth 240,67 g, relative growth 152,05% and FCR 2.36,   and treatment C 235,00 g absolute growth, relative growth 147,04% and FCR 2.41.  Statistic analysis found  abosolute growth of fish in treatment A different significantly compared to treatment B and C.   Treatment A and B had similar effect but different significantly compared to treatment C.  It could be concluded that the use of comfeed was better to increase fish growth and FCR as compared to treatment B and C.   Keywords: growth, nile tilapia, food conversion ratio, commercial feed